2024
DOI: 10.3390/jpm14040434
|View full text |Cite
|
Sign up to set email alerts
|

Variation Analysis in Premenopausal and Postmenopausal Breast Cancer Cases

Ibrahim Halil Erdogdu,
Seda Orenay-Boyacioglu,
Olcay Boyacioglu
et al.

Abstract: Menopausal status affects the prognoses and consequences of breast cancer. Therefore, this retrospective study aimed to reveal the molecular variation profile differences in breast cancer patients according to their menopausal status, with the hypothesis that the molecular variation profiles will be different at premenopausal and postmenopausal ages. Breast cancer patients (n = 254) who underwent molecular subtyping and QIAseq Human Breast Cancer NGS Panel screening between 2018 and 2022 were evaluated retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…More recently, the integration of molecular markers into breast cancer classification systems has allowed for further treatment selection guidance and the identification of novel therapeutic targets. In this Special Issue, Erdogdu et al [ 8 ] investigated the relationship between menopausal status and the histological, molecular and somatic mutation profiles of breast cancer patients. Using next-generation sequencing technology, this interesting paper demonstrated that 94% of both premenopausal and postmenopausal breast cancer patients harboured somatic mutations in established cancer susceptibility genes including TP53 , PIK3CA , BRCA2 , NF1 , PTEN , ATR , CHEK2 , BLM , BRAC1 , PMS2 and ATM .…”
mentioning
confidence: 99%
“…More recently, the integration of molecular markers into breast cancer classification systems has allowed for further treatment selection guidance and the identification of novel therapeutic targets. In this Special Issue, Erdogdu et al [ 8 ] investigated the relationship between menopausal status and the histological, molecular and somatic mutation profiles of breast cancer patients. Using next-generation sequencing technology, this interesting paper demonstrated that 94% of both premenopausal and postmenopausal breast cancer patients harboured somatic mutations in established cancer susceptibility genes including TP53 , PIK3CA , BRCA2 , NF1 , PTEN , ATR , CHEK2 , BLM , BRAC1 , PMS2 and ATM .…”
mentioning
confidence: 99%